MENINGKATKAN LITERASI DIGITAL DAN KETAHANAN TERHADAP HOAKS MELALUI PEMBELAJARAN PPKn: ANALISIS CIVIC KNOWLEDGE, SKILLS DAN DISPOSITION - Sumiatun, Sulistyaningati Purwandari; Muslim, Bukhari; Putri, Ayunda Mahdalena; Listyaningsih (Kajian Moral dan Kewarganegaraan, 2026)
The widespread spread of hoaxes in the digital space poses a serious challenge to the formation of critical and responsible citizens, particularly among students. This phenomenon demonstrates that the issue of hoaxes is not only related to information technology aspects, but also a citizenship issue that demands strengthening digital literacy through education. This study aims to analyze the role of Pancasila and Citizenship Education (PPKn) learning in improving digital literacy and student resilience to hoaxes by strengthening civic knowledge, civic skills, and civic disposition. The study used a qualitative approach with a descriptive analytical research type. The research subjects were grade VIII D students of SMP Negeri 2 Balen who were selected purposely. Data collection techniques included in-depth interviews, learning observations, and analysis of lesson planning documents. The results of the study indicate that contextual and reflective PPKn learning can strengthen students' understanding of hoaxes as a citizenship issue (civic knowledge), develop critical thinking and communication skills in responding to digital information (civic skills), and form an attitude of caution, social responsibility, and commitment to Pancasila values ​​in the use of digital media (civic disposition). However, the implementation of learning still faces challenges such as low initial digital literacy levels among students, limited learning time, the strong influence of social media outside of school, and teacher preparedness. These findings confirm that Civics (PPKn) plays a strategic role in building resilience against hoaxes through an integrated strengthening of digital citizenship competencies